2017
DOI: 10.1002/anie.201703270
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Friedel–Crafts Acylation and Fries Reaction

Abstract: The Friedel–Crafts acylation is commonly used for the synthesis of aryl ketones, and a biocatalytic version, which may benefit from the chemo‐ and regioselectivity of enzymes, has not yet been introduced. Described here is a bacterial acyltransferase which can catalyze Friedel–Crafts C‐acylation of phenolic substrates in buffer without the need of CoA‐activated reagents. Conversions reach up to >99 %, and various C‐ or O‐acyl donors, such as DAPG or isopropenyl acetate, are accepted by this enzyme. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 37 publications
3
79
0
1
Order By: Relevance
“…It was shown that Pp ATase accepts various C‐ or O‐acyl donors such as isopropenyl acetate and transfers an acetyl moiety to a phenolic acceptor in a Friedel–Crafts‐type acetylation . The enzyme complex also shows chemical reaction promiscuity and accepts aniline derivatives as substrates for amide formation …”
Section: Introductionmentioning
confidence: 99%
“…It was shown that Pp ATase accepts various C‐ or O‐acyl donors such as isopropenyl acetate and transfers an acetyl moiety to a phenolic acceptor in a Friedel–Crafts‐type acetylation . The enzyme complex also shows chemical reaction promiscuity and accepts aniline derivatives as substrates for amide formation …”
Section: Introductionmentioning
confidence: 99%
“…6), since we were interested to apply this enzyme for various acyl donors and acceptors (Schmidt et al 2017). Thus, the ATase activity in the following studies was evaluated based on the formation of the C-acetyl product 9 arising from the bioacetylation of model substrate 8 by DAPG.…”
Section: Resultsmentioning
confidence: 99%
“…HCl (3.6 vol%), trans -cinnamaldehyde (3.6 vol%)]. Shake flask cultivation, expression of the wild-type, and recombinant ATase was performed as described previously (Schmidt et al 2017). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps this differentiation will become obsolete in the future. In recent years we have seen an explosion of novel reactions catalyzed by enzymes . The combination of a computational and an experimental approach has become state‐of‐the‐art, which, guided by scientific analysis, enables the design and development of improved catalysts.…”
Section: Au Revoir Uwe Bornscheuermentioning
confidence: 99%